2017
DOI: 10.4093/dmj.2017.41.6.486
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Gestational Diabetes Mellitus in Pregnant Korean Women Based on Abdominal Subcutaneous Fat Thickness as Measured by Ultrasonography

Abstract: BackgroundThis study was performed to verify the correlation between abdominal subcutaneous fat thickness (ASFT) measured by ultrasonography (US) during the first trimester of pregnancy and gestational diabetes mellitus (GDM) of the second trimester in Korean women and to establish a standard of ASFT for predicting GDM.MethodsA total of 333 singleton pregnant women participated in this study. Their ASFT was measured by US during the 10+6 to 13+6 weeks of pregnancy; then a GDM confirmatory test (100 g oral gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…From the included studies, 2,226 and 25,449 pregnant women were GDM and non-GDM, respectively. A total of seven studies were from non-Asian countries [14,[16][17][18][20][21][22], and four were from Asia [13,15,19,23].…”
Section: Characteristics and Quality Assessment Of Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…From the included studies, 2,226 and 25,449 pregnant women were GDM and non-GDM, respectively. A total of seven studies were from non-Asian countries [14,[16][17][18][20][21][22], and four were from Asia [13,15,19,23].…”
Section: Characteristics and Quality Assessment Of Includedmentioning
confidence: 99%
“…The GDM was diagnosed based on two methods among all the studies: five studies used Carpenter/Coustan diagnostic criteria [17-19, 21, 22], five studies used WHO screening criteria (75 g oral glucose tolerance test) [17-19, 21, 22], and one study used self-reports [16]. In these studies, nine studies reported the relationship between maternal central obesity and GDM in the first trimester [13][14][15][16][18][19][20][21] and two reported the relationship in the second trimester [22,23]. Six studies adopted WC or WHR [13][14][15][16][17][18], two used visceral adipose tissue depth (VAT) [20,21], two used BFI or FMP [22,23], and one used maternal SFT to measured maternal central obesity [19].…”
Section: Characteristics and Quality Assessment Of Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…Martin et al reported that a VAT above the upper quartile of the normal range in the 1st trimester of pregnancy was significantly more frequent in cases than in controls. Only one study conducted by Yang et al on 333 singleton pregnancies in the 1st trimester reported that SAT was a statistically significant predictor of GDM. In a recent prospective study, De Souza et al measured SAT, VAT and total adipose tissue depth in a cohort of 485 women using a different ultrasound technique at 11‐14 weeks of gestation.…”
Section: Discussionmentioning
confidence: 98%
“…Yang et al [ 10 ] measured ASFT at 1st trimester and performed 2-step OGTT at 2nd trimester in about 300 pregnant women. The authors found that ASFT is highly correlated with the risk of GDM than well-established risk factors such as age and BMI, and suggested a cut-off value to discriminate the high-risk groups.…”
mentioning
confidence: 99%